Animal Protection Laws of Singapore and Malaysia - SEE, Alvin W. L. (Institutional Knowledge at Singapore Management University, 2013)
This article offers an overview and assessment of the laws relating to the protection of animals in Singapore and Malaysia. The focus is on identifying the interpretations of the statutory offences of cruelty that will best promote their objectives and effectiveness.